PAKU ALAM V: SANG ARISTO-MODERNIS DARI TIMUR - Sudibyo, Sudibyo (History Department, Semarang State University and Historian Society of Indonesia, 2015)
This paper recites Paku Alam V figures as an ambiguity subject and a cultural paradox. He lived in a kingdom economic crisis and a rapid flow of changes in politics, economy, laws, and lifestyle aspects which is caused by other colonial social elements. The analysis focuses on psychological, religious, and cultural aspects which form his personality. To achieve the goal, it uses post colonialism concerning in contact zone, textual studies and historical context. The textual studies are used to explain the role modernization in genealogy, consistence, and Paku Alam V mind revolution. The historical context is used to explain the historical background, especially related to zeitgeist, when Paku Alam V implemented his ideas.Keywords: aristocrat, paradox, text, context. Tulisan ini mengkaji sosok Paku Alam V sebagai subjek ambiguitas dan paradoks kebudayaan. Ia hidup di tengah krisis ekonomi kerajaan dan arus perubahan yang deras di bidang politik, ekonomi, hukum dan gaya hidup yang dihembuskan oleh kekuasaan dan elemen-elemen masyarakat kolonial lainnya. Analisis difokuskan pada aspek-aspek psikologis, religious, dan kultural yang membentuk pribadinya. Untuk mencapai tujuan itu, digunakan teori poskolonialisme tentang zona kontak dan kajian teks serta konteks sejarah. Kajian teks digunakan untuk menjelaskan peran modernisasi dalam genealogi, konsistensi, dan evolusi atau revolusi pemikiran P.A. V. Konteks sejarah digunakan untuk menjelaskan latar belakang sejarah, khususnya yang berkaitan dengan zeitgeist saat P.A. V mengimplementasikan gagasan-gagasannya. Kata kunci: aristrokat, modernis, paradoks, teks, konteks